Bringing agile practice to the classroom: Student voices of third-year major project implementation. Issue 5 (23rd December 2016) - Kumar, Deepak; Govender, Irene
Abstract : Agile practices are the current trend in the software industry, so it is, therefore, pertinent that students not only learn but practise agile development in the learning environment. Adapting to a different approach such as agile practices in software systems development has been a challenge for both students and lecturing staff. This study examined the underlying challenges and experiences of students in using the agile approach to software development in a project course. A mixed-methods approach was followed with focus group interviews and a survey instrument used to determine the students' experiences of the agile approach to software development. The results reflected an intention to use agile practices in future and enthusiasm in using agile practices in learning. In addition, it was found that more programming expertise was needed for some students without the requisite programming knowledge. These findings have implications for structuring courses more effectively for undergraduate modules.